The ranch - Steel, Danielle (New York, U.S.A. : Dell Book, 1997)
They had been inseparable as roommates in college, Mary Stuart, Tanya, adn Zoe. But in the more than twenty years that followed, the three had moved on with theirs lives. By chance, each would find herself alone for a few weeks one summer, wrestling with both the present and the past. At a sprawling ranch in the foothills of Wyoming´s Grand Tetons, the three women come together and find courage, healing, and truth, and reach out to each other once againg.
Chapter 1 Chapter 2 Chapter 3 Chapter 4 Chapter 5 and others 16 chapters more
Is Americas #1 Bestseller
Keywords: ENGLISH LITERATURE; STORY